1988
DOI: 10.1073/pnas.85.7.2353
|View full text |Cite
|
Sign up to set email alerts
|

Close correlation between restriction fragment length polymorphism of the L-MYC gene and metastasis of human lung cancer to the lymph nodes and other organs.

Abstract: Close correlation between restriction fragment length polymorphism of the L-MYC gene and metastasis of human lung cancer to the lymph nodes and other organs (cancer ABSTRACTRestriction length fragment polymorphism of the L-MYC gene was examined in DNAs from lung cancer tissues and normal tissues of 51 Japanese patients with lung cancer. In individual patients, no difference was seen between the restriction length fragments of the two alleles of L-MYC [6-kilobase (kb) and 10-kb fragments in EcoRI digests] in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
4
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 10 publications
0
49
4
1
Order By: Relevance
“…However, a close correlation with the stage of differentiation of the tumours and the L-myc RFLP was observed. In contrast Kakehi and Yoshida (1989), in renal cancers, and Kawashima et al (1988), in lung cancers, did not observe such an association with the grade of tumour cell differentiation. An interesting question is how the presence of the S allele of L-myc could be related to the stage of differentiation selectively in oral cancers.…”
Section: Correlation Of L-myc Rflp With Clinical Patternmentioning
confidence: 60%
See 3 more Smart Citations
“…However, a close correlation with the stage of differentiation of the tumours and the L-myc RFLP was observed. In contrast Kakehi and Yoshida (1989), in renal cancers, and Kawashima et al (1988), in lung cancers, did not observe such an association with the grade of tumour cell differentiation. An interesting question is how the presence of the S allele of L-myc could be related to the stage of differentiation selectively in oral cancers.…”
Section: Correlation Of L-myc Rflp With Clinical Patternmentioning
confidence: 60%
“…RFLP studies of the L-myc gene have demonstrated a close association of the S (6.6 kb) fragment with metastatic potential in lung cancer (Kawashima et al, 1988), colon and stomach cancers (Kawashima et al, 1987), and renal cell carcinomas (Kakehi & Yoshida, 1989). These studies indicated that the L (10.0kb) fragment was an indicator of better prognosis in the cancers.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Scattered reports have suggested that individuals bearing the`short' (S) allele either have an increased incidence of certain tumors and/or that such tumors manifest a more aggressive behavior. The associated neoplasms include soft-tissue sarcomas (Kato et al, 1990), oral cancers (Saranath et al, 1990), colorectal cancers (Young et al, 1994), nonHodgkin's lymphoma (Crossen et al, 1994), breast cancer (Champeme et al, 1992), and non-SCLC lung cancer (Kawashima et al, 1988). In contrast, at least one report has suggested that the`SS' genotype protects against hepatocellular cancer (Taylor et al, 1993).…”
Section: Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%